Análisis de las actitudes de los estudiantes hacia la matemática en la educación básica superior en la Unidad Educativa “La Providencia” periodo enero 2017 – abril 2017 - Aguirre Guashpa, Karla Estefanía (2017)
This research is focused in the students' attitudes towards mathematics at U.E "La Providencia". Some of the most common attitudes and behaviors into the mathematics learning process; the feelings that the students demonstrate are: rejection, denial, frustration, avoidance, etc. It is necessary to understand and be aware, since the teaching work, certain behaviors, failures, fears, from the students as well as their perception about the teacher who teaches it. Their attitudes depend on three components: Cognitive: expressions of thought, conceptions and beliefs, about the subject. Affective: expressions of feeling. It includes all of those emotions and feelings that causes mathematics, Behavioral: expressions of action or intention. The design of the research is non-experimental, the type of research is descriptive and field. There was no sample, it was decided to work with the population of 106 students, it is accomplished that the students of the U.E "La Providencia" in the analyzes developed have indicated that the attitude towards mathematics does not vary in the three dimensions because they have a positive attitude. It is recommended to develop out prevention and intervention programs in Mathematics learning difficulties and emotional education in this area, because they help to appeal and like for the subject, improve the attitudes, beliefs and emotional reactions from students experience towards Mathematics.